2008
DOI: 10.1021/cm801723b
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedral Chain Order in the Sr2Fe2O5 Brownmillerite

Abstract: The crystal structure of the Sr 2 Fe 2 O 5 brownmillerite has been investigated using electron diffraction and high resolution electron microscopy. The Sr 2 Fe 2 O 5 structure demonstrates two-dimensional order: the tetrahedral chains with two mirror-related configurations (L and R) are arranged within the tetrahedral layers according to the -L-R-L-Rsequence, and the layers themselves are displaced with respect to each other over 1/2[111] or 1/2[111 j ] vectors of the brownmillerite unit cell, resulting in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 23 publications
(62 reference statements)
8
127
0
Order By: Relevance
“…15 The Fe(Mn)ÀO bond length, 1.94539(2) Å, is very close to the average FeÀOa n dM n ÀOd i s t a n c e si n A 2 Careful inspection of the neutron diffraction data revealed shoulders appearing on almost every major peak, shifted systematically to smaller d spacings; see the inset in Figure 2b. This signaled the presence of a slight amount of another cubic phase with similar composition but smaller cell parameters, which was confirmed by a two-phase Rietveld refinement.…”
Section: ' Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…15 The Fe(Mn)ÀO bond length, 1.94539(2) Å, is very close to the average FeÀOa n dM n ÀOd i s t a n c e si n A 2 Careful inspection of the neutron diffraction data revealed shoulders appearing on almost every major peak, shifted systematically to smaller d spacings; see the inset in Figure 2b. This signaled the presence of a slight amount of another cubic phase with similar composition but smaller cell parameters, which was confirmed by a two-phase Rietveld refinement.…”
Section: ' Introductionmentioning
confidence: 67%
“…It is noteworthy that, in the above cases, the change in A-site cation results in a change in space group, whereas the general structural type remains the same. Both Ca 2 (99.9% Cerac) that were mixed and pressed into pellets. The pellets were annealed at 1250°C in an argon atmosphere for a total time of ∼100 h and were then slowly cooled to room temperature.…”
Section: ' Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that different ordering of tetrahedral chains is characteristic of the brownmillerite structure, which in turn leads to different space symmetry groups: Icmm, Ibm2, and Pnma [17]. Figure 8 shows the results of modeling the diffraction patterns using different space groups.…”
Section: Resultsmentioning
confidence: 99%
“…This was challenged, however, by transmission electron microscopy results showing clear intralayer alternation of tetrahedral chains. 33 Additionally, more recent neutron diffraction experiments on single crystals grown by the floating zone method have indicated that P bcm is indeed the preferred structure type for Sr 2 Fe 2 O 5 . 18,19 Furthermore, all of these recent experiments are supported by the aforementioned results of our ab initio calculations; the small energy difference between the P bcm and I2bm structures, however, indicate that intergrowths of the phases is not out of the question.…”
Section: A Polyhedral Rotation Definitionsmentioning
confidence: 99%